Genotoxicity of Silver Nanoparticles synthesized by Laser Ablation Method in Vivo - Tawfeeq, Amer T. (Iraqi Journal of Cancer and Medical Genetics, 2015)
This research was conducted to evaluate three main methods usually used to assess cellular DNA damage in genotoxicity assays. These methods were single cell gel electrophoresis (comet assay), micronucleus formation, and DNA fragmentation assay. Nanoparticles genotoxicity is a subject of compelling immediate action as a result of wide application of nanotechnology in many sectors which in contact with humane health. The mentioned methods were used to assess the genotoxicity of silver nanoparticles in vivo. Silver nanoparticles were synthesized by laser ablation of pure silver plate submerged in double distilled water. The synthesized nanosilver was characterized with UV-Visible spectroscopy and atomic force microscope. After its characterization, silver nanoparticles were injected subcutaneously in to BALB/c mice at 200 µg/ kg BW for two different periods of time, one week and two weeks in daily manner. After the end of injection the animals were sacrificed and their bone marrow cells, lymphocytes, and spleen cells were collected. DNA damage in these cells was assessed using the three mentioned methods. Results indicated that the three types of DNA damage assessment methods were capable to detect the genotoxicity of silver nanoparticles in the treated animals. Spleen cells were the less DNA damaged cells as indicated with the three assays in the first week of injection. Lymphocytes and bone marrow cells was effected in more aggressive manner.